Pelatihan Penguatan Identitas Produk di Instagram pada Kelompok Usaha Bersama Ulva Sari: Strengthening Product Identity Training on Instagram at the Joint Business Group Ulva Sari - Vidiadari, Irene Santika; Sanjaya, I Putu Sugiartha; Purwijantiningsih, LM. Ekawati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) face challenges in promoting their products, especially on social media. Social media offers several advantages, including a broad reach, low cost, easy access, and the ability to provide content recommendations tailored to user searches. We should capitalize on these advantages to effectively promote our products. However, MSME products require a distinct product identity to ensure easy recall by their audience and potential consumers. This article discusses assistance in building a product identity on social media for Kelompok Usaha Bersama (KUB) Ulva Sari, located in the Tepus District, Gunung Kidul. This activity includes materials on social media and its advantages, the importance of using social media for product promotion, building a product identity through logo and color elements, and creating an Instagram business account, along with an introduction to its features. The results of this community service activity include determining colors and logos as product identities, creating a special Instagram account for KUB Ulva Sari products, developing a website to display basic product information, and assigning two social media administrators to manage the account.